FROM PARTICIPATION TO PROFICIENCY: HOW ENGLISH CLUB ACTIVITIES ENHANCE NURSING STUDENTS’ ENGLISH SKILLS - Zakaria, Juliana; Nushur, Rizki Dhian; Yanti, Nurlayli; Che Abdullah, Che Azunie (ICALCOM, 2026)
English language learning in nursing colleges plays a crucial role because students are required to master language skills that support academic and professional competencies. However, formal classroom learning often fails to develop practical skills, necessitating supporting strategies such as extracurricular activities. This study aims to analyze the contribution of the English Club to improving the English language skills of nursing students at the Academy of Nursing Kesdam Iskandar Muda Banda Aceh (AKIMBA). The research method used is descriptive quantitative with correlation analysis technique. The research sample consisted of 50 students who actively participated in the English Club. Data were collected through a closed questionnaire to determine student perceptions and documentation of Study Result Card (KHS) scores to measure learning achievement. The results showed that student perceptions of the English Club were very positive with an average of 82.3% (strongly agree category). The Product Moment correlation test produced a value of r = 0.550 with a sig. 0.00 < 0.05, which means there is a positive and significant relationship between student participation in the English Club and English learning achievement. This finding confirms that student activeness in the English Club plays an important role in improving English mastery, while also fostering motivation, discipline, and self-confidence. Thus, the English Club can be used as an effective supporting strategy in the context of English for Specific Purposes (ESP) in the nursing field.